Temporal and spatial variability of the most important phenological phases of birch in the Czech Republic - Hájková, L., Czech Hydrometeorological Institute, Ústí nad Labem (Czech Republic); Sedláček, V., Czech Hydrometeorological Institute, Ústí nad Labem (Czech Republic); Nekovář, J., Czech Hydrometeorological Institute, Praha 4 - Komořany (Czech Republic) (Folia oecologica, 2007)
Phenology is the study of the times of recurring natural phenomena in plants and animals. The Czech Meteorological Service launched its phenological observations in 1940, with a whole data-providing network, including the archives from the year 1923. Today the Czech Hydrometeorological Institute (CHMI) operates with a network of phenological stations encompassing field crops, fruit trees and wild plants, according to the Methodical instructions number 2, 3, 10. There are also observed several very important allergenic species from which birch (Betula verrucosa Ehrh.) has been chosen for the subject of this case study - as one of the most frequent allergenic plants in Europe, including the Czech Republic. Its pollen grains are the most important allergen. Observing phenological phases (flower buttons visible, beginning and end of flowering) is important for identification of the pollen season. At wild plant stations, there are observed these phenophases in Betula verrucosa Ehrh: sprouting, first leaves, full leaves, flower buttons visible, beginning and end of flowering, bud creation, lignification of sprouts, yellowing of leaves, defoliation and ripening of fruits. Temporal and spatial variability in the chosen phenophases (sprouting, first leaves, full leaves, flower buttons visible, beginning and end of flowering) was explored with using statistical (basic statistical characteristics) and GIS methods for the periods 1992-2006 and 1992-2007 with respect to allergenic importance of the phenophases. Temporal variability was monitored at the phenological stations Lednice (48 degree 48 minutes N, 16 degree 48 minutes E, 165 m asl) and Pernink (50 degree 22 minutes N, 12 degree 47 minutes E, 860 m asl), the spatial variability at 44 stations with MASL (mean above sea level) ranging from 155 m (Doksany - Polabská nížina) to 1102 m (Filipova Huť - Šumava). The results are presented in form of tables and maps. In this case study we observed the following shifts in phenophases (lowland in comparison with mountain): sprouting (22.6 days), first leaves (19.8 days), full leaves (21.6 days), flower buttons visible (26.5 days), beginning of flowering (27.2 days), end of flowering (25.4 days).